Grafting of poly(triethylene glycol dimethacrylate) onto chitosan by ceric ion initiation - Yılmaz, Elvan; Adalı, Tülay; Yılmaz, Osman (Elsevier, 2007)
Grafting of poly(triethylene glycol dimethacrylate) (poly(TriEGDMA)), onto chitosan by ceric ion initiation has been investigated. The grafting conditions were optimized by studying the effect of monomer and initiator concentrations as well as time and temperature. Products with lower grafting yields (90–261%) were water and acid soluble. Those with higher grafting yields (350–868%) were insoluble, indicating a cross linked structure. Chitosan-graft- poly(TriEGDMA) products had a lower thermal stability than chitosan as revealed by DSC analysis. C-13 NMR and FTIR analyses suggested a grafting mechanism that proceeds via oxidation and chain scission of chitosan. The products are degraded by the enzymes lysozyme, lipase and α-amylase–protease.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Cerium ammonium nitrate; Copolymerization; Water soluble; Cross linking; Oxidation